(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the current study was to examine the behavioural problems in school going adolescents of Kashmir utilizing Bio-ecological systems model. Participants of the study were 286 adolescents selected purposively from different higher secondary institutions of Srinagar; Baramulla and Sopore. Behavioural problems were defined as measured by Behavioural Problem Monitor (BPM-YF). The study found significant correlation between the age of the adolescents and the behavioural problems. However an insignificant association was found between gender and the adolescent behavioural problems. Results revealed a significant correlation between contextual processes of family and behavioural problems in adolescents. Further the model ANOVA showed that family functioning can significantly predict behavioural problems in adolescents of Kashmir.